Associations between LEP, DGAT1 and FABP4 gene polymorphisms and carcass and meat traits in Nelore and crossbred beef cattle - Curi, Rogerio Abdallah [UNESP]; Chardulo, Luis Artur Loyola [UNESP]; Arrigoni, Mario de Beni [UNESP]; Silveira, Antonio Carlos [UNESP]; Oliveira, Henrique Nunes de [UNESP] (Elsevier B.V., 2011)
The aim of this study was to estimate the segregation of leptin (LEP), diacylglycerol O-acyltransferase (DGAT1) and fatty acid-binding protein 4 (FABP4) gene polymorphisms in Nelore (Bos indicus) and Nelore x Bos taurus beef cattle, and to evaluate their effects on carcass and meat traits. A total of 300 animals were genotyped for the LEP/BsaAl (Y_11369.1: g.1620G > A), DGAT1-VNTR (18-bp repeat element in the promoter region) and FABP4/MspA1I (AAFC_01136716.1:g.7516C > C) polymorphisms and phenotyped for rib eye area, backfat thickness (BT), intramuscular fat, shear force, and myofibrillar fragmentation index. The allele substitution effects for each of the polymorphisms on the traits of interest were estimated by regression on the number of copies of a particular allele using the General Linear Model procedure. To keep the experiment wise error rate to the specified level, the Bonferroni adjustment was applied. Although the LEP/BsaAl polymorphism has shown segregation for association studies in Nelore cattle [f(A) = 0.351], no associations were observed between its alleles and the traits analyzed. The DGAT1-VNTR was found to be polymorphic in Nelore cattle, as well as a potential association with BT. In addition to being non-informative in Nelore animals (allele C was found to be fixed), the FABP4/MspA1I polymorphism showed no association with the studied traits in crossbred animals. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Molecular markers; candidate gene; Fat deposition; Meat tenderness; Zebu